PENETRASI PASAR HASIL PERTANIAN KEBUNSAYUR SURABAYA - Eliyana, Firda; Nurhadi, Eko; Yektiningsih, Endang (Berkala Ilmiah AGRIDEVINA, 2020)
Kebun sayur Surabaya is the first hydroponic vegetable producer in the city of Surabaya as well as a supplier of fresh vegetables in several segments of hotels, restaurants and cafes in Surabaya. To penetrate this segment is not easy, it requires a long process and various efforts to be able to penetrate the segment amid increasingly fierce market competition. This study aims to analyze: 1) market penetration conducted by Kebunsayur Surabaya towards hotels, restaurants and cafes, 2) differences in the absorption capacity of Kebunsayur Surabaya lettuce in hotels, restaurants and cafes, 3) Market penetration strategy that has been carried out by Kebunsayur Surabaya towards hotels, restaurants and cafes, 4) Market share controlled by Kebunsayur Surabaya in hotels, restaurants and cafes in Surabaya. The results showed that: (1) The form of market penetration carried out by Kebunsayur towards hotels, restaurants and cafes was by attracting non-users or potential consumers who were in their market environment (2) there were differences in the absorption of lettuce between hotels, restaurants and cafes in Kebunsayur Surabaya, (3) the market penetration strategy that has been carried out by Kebunsayur is in accordance with the Ihalauw 2017 theory, (4) The market share of Kebunsayur lettuce at Resto A has decreased from 39% (before the pandemic) to 29% (during the pandemic), while the lettuce from Kebunsayur is able to control 100% market share in JW Marriot and Cattura Expresso DOI : https://doi.org/10.33005/adv.v9i2.2455